2018
DOI: 10.1016/j.addbeh.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette advertising exposure in e-cigarette naïve adolescents and subsequent e-cigarette use: A longitudinal cohort study

Abstract: This study provides one of the first longitudinal examinations demonstrating that exposure to e-cigarette advertising on social networking sites among youth who had never used e-cigarettes increases the likelihood of subsequent e-cigarette use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
83
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 32 publications
(42 reference statements)
12
83
1
1
Order By: Relevance
“…All dual and triple substance combinations including this behaviour rose in prevalence towards the end of the examined period, with concurrent vaping and drinking particularly common. The association between e-cigarettes and alcohol, previously observed in other studies ( Morean et al, 2016 ; Schlienz & Lee, 2018 ; Taylor et al, 2017 ), together with data on social media trends ( Camenga et al, 2018 ; Chu et al, 2018 ; Sampasa-Kanyinga & Hamilton, 2018 ), indicates that use of the former is now a social activity ( Pepper et al, 2017 ; Yule & Tinson, 2017 ). This is particularly concerning not only in light of potential feedback effects due to the previously discussed outsize effects of peer behaviour, but also because e-cigarette use has been shown to increase the risk of cigarette smoking ( Barnett et al, 2015 ; Bold et al, 2018 ; Hammond et al, 2017 ), which also often co-occurs with alcohol use in social situations ( Berg et al, 2018 ; Gubner, Thrul, Kelly, & Ramo, 2018 ; Silveira et al, 2018 ), adding an additional layer of risk.…”
Section: Discussionsupporting
confidence: 60%
“…All dual and triple substance combinations including this behaviour rose in prevalence towards the end of the examined period, with concurrent vaping and drinking particularly common. The association between e-cigarettes and alcohol, previously observed in other studies ( Morean et al, 2016 ; Schlienz & Lee, 2018 ; Taylor et al, 2017 ), together with data on social media trends ( Camenga et al, 2018 ; Chu et al, 2018 ; Sampasa-Kanyinga & Hamilton, 2018 ), indicates that use of the former is now a social activity ( Pepper et al, 2017 ; Yule & Tinson, 2017 ). This is particularly concerning not only in light of potential feedback effects due to the previously discussed outsize effects of peer behaviour, but also because e-cigarette use has been shown to increase the risk of cigarette smoking ( Barnett et al, 2015 ; Bold et al, 2018 ; Hammond et al, 2017 ), which also often co-occurs with alcohol use in social situations ( Berg et al, 2018 ; Gubner, Thrul, Kelly, & Ramo, 2018 ; Silveira et al, 2018 ), adding an additional layer of risk.…”
Section: Discussionsupporting
confidence: 60%
“…Viewing e-cigarette social media content has been associated with similar outcomes in prior research, although prior research was correlational and most studies did not involve adolescents or distinguish between peer-generated content and advertisements. [25][26][27] Unexpectedly, e-cigarette content exposure (heavy or light) did not interact with content source (peer-generated or advertisement) to influence ecigarette use outcomes. Viewing advertisements, however, did result in greater willingness, intention, attitudes, and norm perceptions.…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…However, social media posts generated by other young people (i.e., peers) may have an even stronger influence than advertisements on adolescents' e-cigarette use. Three studies [25][26][27] have found associations between e-cigarette use and exposure to e-cigarette content (i.e., advertisements and/or peer-generated posts) on social media; however, these studies were correlational and two 25,26 surveyed college students. College students' behavior may be less influenced by peers than adolescents' behavior, as the impact of social norms can decrease with age.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Higher levels of online engagement were associated with greater susceptibility to use a tobacco product among tobacco never users as well as current and past tobacco users. A longitudinal study of 1742 never e-cigarette users reported that exposure to e-cigarette advertisements on social media had an effect on subsequent use of e-cigarettes 29. Social media has also been exploited in marketing alcoholic beverages with a transition in emphasis from exposure to engagement noted over recent years.…”
Section: Discussionmentioning
confidence: 99%